Predicting high blood metal ion concentrations following hip resurfacing. - Matharu, G; Berryman, F; Brash, B; Pynsent, P; Treacy, R; Dunlop, D (Wichtig Editore, 2015)
To determine whether gender, femoral head size, acetabular inclination, and time since surgery predicted high blood metal ion concentrations following Birmingham Hip Resurfacing (BHR).BHR patients with unilateral bearings at one specialist centre with blood cobalt and chromium concentrations measured up to May 2013 were included. This comprised a mixed (at-risk) group including symptomatic patients and asymptomatic individuals with specific clinical and/or radiological findings. Blood sampling was at a mean of 7.5 years (range 1-15.4 years) postoperatively.Of 319 patients (mean age 49.3 years; 53% male), blood metal ions greater than 7 µg/l were observed in 9% (n = 28). Blood metal ions were significantly higher in females (pandlt;0.001), femoral head sizes ≤48 mm (pandlt;0.01), and cup inclinations andgt;55° (pandlt;0.001). Linear regression demonstrated femoral head size was responsible for the highest proportion of variance in blood metal ions (cobalt pandlt;0.001, R2 = 8%; chromium pandlt;0.001, R2 = 11%). Analysis of femoral head size and inclination together demonstrated 36% of BHRs with head sizes of 38-44 mm and inclination andgt;55° had blood metal ions andgt;7 µg/l. BHR 10-year survival for this at-risk group was 91% (95% confidence intervals 86.0%-95.0%) with 30 hips revised.If blood metal ions are used to screen hip resurfacing patients for adverse reactions to metal debris it is recommended those with small femoral head sizes (38-44 mm) and high acetabular inclinations (andgt;55°) are targeted. These findings require validation in other cohorts as they may not be applicable to all hip resurfacing devices given the differences in radial clearance, coverage arc, and metallurgy.